Kegagalan Optimalisasi Pengelolaan Aset Pasar Modern Sorek Satu di Kabupaten Pelalawan - Alziad Saputra; M. Rafi (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2026)
The management of Pasar Modern Sorek Satu, as regulated in the Regent Regulation of Pelalawan Regency Number 31 of 2023. However, in its implementation, the management of the market continues to face various problems that affect the low level of kiosk utilization and trading activities. This study aims to analyze the optimization of the management of Pasar Modern Sorek Satu by the Office of Cooperatives, Small and Medium Enterprises, Industry, and Trade of Pelalawan Regency in 2024, as well as to identify the factors influencing it. The research employs a descriptive qualitative approach, with data collected through interviews and documentation, which are analyzed using an interactive analysis model. The results indicate that the management of Pasar Modern Sorek Satu has not yet been optimal, as evidenced by the non-compliance of the kiosk rental system with existing regulations, high rental fees that are not proportional to kiosk size, low occupancy rates, and weak security and maintenance of market facilities. The driving factors for optimization include the determination of kiosk rental values based on KPKNL valuation and the existence of a Technical Implementation Unit (UPTD) as the technical management unit. Meanwhile, the inhibiting factors include inconsistencies in the rental system, imbalance between kiosk size and rental costs, weak security and maintenance of infrastructure, and high rental fees that contribute to the low utilization rate of the market. Unlike previous studies, this research integrates the institutional perspective of local government with the socio-economic realities of traders at Pasar Modern Sorek Satu in 2024. As an academic recommendation, this study is expected to serve as a reference for the development of locally contextualized modern market governance studies and to enrich the literature on the evaluation of market management policies implemented by local governments.